Talking in the cloud: How to organize a virtual book club - Moreno Mulas, María Antonia; García-Rodríguez, Araceli; Gómez-Díaz, Raquel (Revista General de Información y Documentación, 2017)
Book clubs are one of the most effective ways to get new readers and to keep them. This is true even for online ones as long as they are designed, organized, managed and dynamized in the right way. This article analyzes a selection of online book clubs offered by Spanish libraries in order to point out the main aspects in their management. Furthermore, they are classified according to the medium or forum of conversation in which they are made and the book club in Nubeteca, a project of Fundación Germán Sánchez Ruipérez and Diputación de Badajoz, is included as a model..
Keywords: Public Libraries; Virtual Book Club; Book Club in the cloud; Promoting Reading